Ultrasound of the Distal Insertions of the Ankle and Foot Tendons with Anatomical Correlation: A Review. Issue 3 (August 2018) - De Maeseneer, Michel; Madani, Hardi; Lenchik, Leon; De Mey, Johan; Provyn, Steven; Shahabpour, Maryam
The distal insertions of the tendons crossing the ankle as well as the tendons originating in the foot are less well known by radiologists. We review the anatomy and ultrasound appearance of these insertions using our own cadaveric sectioning and dissection. The ultrasound images were correlated with anatomical slices. Occasionally magnetic resonance images were also used for better understanding. Understanding the normal appearance of these tendon insertions is important for diagnosing pathology in this region.